Az államutódlás egyes kérdései felbomlás és újraegyesítés során - Szávai, Ferenc (Acta Scientiarum Socialium, 2016)
Some Questions of State Succession in Cases of Dissolution and Reunification.Multinational state forms persisted during the 20th century, yet at the same time federal formations came to be and came to an end. The 1978 and 1983 regulations of dissolution and reunification concerned international agreements, state property and public debt. In this paper we present the post 1945 cases, the problems of property law and state succession in the case of the Soviet Union, Czechoslovakia, Yugoslavia and German reunification.
Keywords: dissolution; regulations of dissolution and reunification; international agreements; state property and public debt